2014
DOI: 10.1016/j.proeng.2014.10.344
|View full text |Cite
|
Sign up to set email alerts
|

Electro-thermo-mechanical Finite Element Analysis on DC Pulse Resistance Pressure Sintering Process of Zirconia Part

Abstract: Some difficulties have arisen on appropriate design of the graphite dies, on applying the DC pulse resistance pressure sintering process, which is more efficient process than other conventional sintering processes such as hot pressing process, to a complex shaped part of non-conductive ceramics powder such as zirconia powder. In the present paper, the non-steady electro-thermomechanical finite element analysis of the sintering process of the zirconia cylindrical can was performed. As a result, it was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Kubota et al used double‐punch tooling to sinter a zirconia can. [ 12 ] Voisin et al achieved homogeneous densification using a set of punches with different length. [ 13 ] The authors demonstrated the sintering of a turbine blade made of IRIS (Ti 48 Al 48 W 2 Nb 2 ) powder alloy.…”
Section: Tooling Designmentioning
confidence: 99%
“…Kubota et al used double‐punch tooling to sinter a zirconia can. [ 12 ] Voisin et al achieved homogeneous densification using a set of punches with different length. [ 13 ] The authors demonstrated the sintering of a turbine blade made of IRIS (Ti 48 Al 48 W 2 Nb 2 ) powder alloy.…”
Section: Tooling Designmentioning
confidence: 99%
“…A structural mechanical module was set for the mechanical simulation and the structures were modelled as a linear elastic materials using the micro-CT and SEM morphological data. The models were defined with an elastic modulus, Poisson's ratio and density of 110 GPa, 0.34 and 4500 kg/m 3 for the Ti 6 Al 4 V, 200 GPa; 0.30 and 6000 kg/m 3 for the ZrO 2 ; 3.76 GPa, 0.38 and 1300 kg/m 3 for PEEK (Bartolomeu et al, 2019;Kubota et al, 2014;Garcia-Gonzalez et al, 2015). Finite element meshes were generated for each model using tetrahedral elements following the same strategy as reported in literature (Bartolomeu et al, 2019), assuring the convergence of the numerical simulation following a parametric study.…”
Section: Mechanical Analysesmentioning
confidence: 99%